مفهوم ووعى الشباب السعودى برؤية المملكة العربية السعودية 2030 : دراسة ميدانية على طلاب جامعة الملك عبدالعزيز - مطاوع، أنمار حامد Mutawa, Anmar Hamid (جامعة الملك عبدالعزيز, 2018)
The aim of this study was to know the most significant sources of information that university students throughout The Kingdom of Saudi Arabia (King Abdul-Aziz University as a model) get on Saudi Arabia’s 2030 Vision. To achieve that, a questionnaire has been designed to cover several axes: traditional and new media and other information sources such as conferences, seminars and lectures. The research population represented is both male and female, a sample of 150 students randomly selected. The study shows that the main source of information students are gaining from regarding the 2030 vision is through social media, mainly Twitter. The study also found that still, students are getting information from traditional media, mainly TV. The study found that there is a positive conception that exists amongst students on the implementation of the 2030 Vision and its goals being directed equally to all segments of society, as well as the extent of it’s direct impact on the future of the kingdom. In addition, the study also found that the students are very positive towards the new economic plan and believe that oil will no longer be the main source of income for Saudi Arabia by 2030. While those ratios declined significantly when it came to the clarity on the Vision’s goals, it’s necessary that we begin working on clarifying the vision and its objectives even more to all sections of society. Finally, the study also showed that there is a strong correlation between the rate of follow-up students and relying on both traditional and new media to get their information on The Kingdom of Saudi Arabia’s Saudi Vision 2030.
هدفت الدراسة إلى الكشف عن مصادرة المعلومات التي يستقي منها طلاب وطالبات الجامعة – جامعة الملك عبدالعزيز أنموذجاً – المعلومات المتعلقة برؤية المملكة 2030. ولتحقيق ذلك تم تصميم استبانة موزعة على عدة محاور: وسائل الإعلام التقليدية، وسائل الإعلام الجديد، ومصادر المعلومات الأخرى؛ مثل: المؤتمرات والندوات والمحاضرات. تكونت عينة الدراسة من (150) طالباً وطالبة تم اختيارهم عشوائياً. وأشارت الدراسة إلى أن أكثر مصادر المعلومات الخاصة بالرؤية هي وسائل التواصل الاجتماعي؛ تويتر تحديداً. بينما تأتي بعض تلك المعلومات أيضاً عن طريق وسائل الإعلام التقليدي؛ التلفزيون تحديداً. وقد وجدت الدراسة أن المفهوم إيجابي لدى الطلاب والطالبات فيما يتعلق بواقعية الرؤية في أهدافها، وشمولها لجميع شرائح المجتمع ومدى تأثيرها المباشر على مستقبلهم المهني، حيث كانت النسب مرتفعة. كما أن نسبة قناعتهم بأن المملكة لن تعتمد على النفط كمصدر أساس للدخل بحلول عام 2030م كانت عالية. فيما انخفضت تلك النسب بشكل كبير فيما يتعلق بمدى وضوح أهداف الرؤية لهم. وهنا تأتي ضرورة العمل على توضيح الرؤية وأهدافها للأسرة والمجتمع بكافة شرائحه. كما اتضح من خلال الدراسة أن هناك علاقة ارتباطية بين معدل متابعة الطلاب والطالبات لوسائل الإعلام التقليدية والجديدة والاعتماد عليها في استقاء المعلومات عن الرؤية.
Keywords: الوعى -- الشباب السعودى -- وسائل الإعلام -- التواصل الاجتماعى -- التحول الوطنى -- رؤية المملكة العربية السعودية 2030 -- طلبة الجامعات -- جامعة الملك عبدالعزيز